2016
DOI: 10.1007/s10900-016-0290-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Pertussis and Tetanus Vaccination Status Among Foreign-Born Adults Living in the United States

Abstract: Pertussis is a common vaccine-preventable disease (VPD) worldwide. Its reported incidence has increased steadily in the United States, where it is endemic. Tetanus is a rare but potentially fatal VPD. Foreign-born adults have lower tetanus–diphtheria–pertussis (Tdap) and tetanus–diphtheria (Td) vaccination coverage than do U.S.-born adults. We studied the association of migration-related, socio-demographic, and access-to-care factors with Tdap and Td vaccination among foreign-born adults living in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 25 publications
(33 reference statements)
5
14
0
Order By: Relevance
“… 14–17 Further, health status, presence of chronic conditions, and receiving advice from health care professionals are documented factors associated with vaccine uptake. 17 Overall, results from our multivariable regression models were generally consistent with several previous studies that have reported associations between demographic characteristics, health status, and/or health care utilization behaviors and receipt of influenza vaccination, 14–17 Tdap vaccination, 15,18 HZ vaccination, 9,19 or pneumococcal vaccination. 20 …”
Section: Discussionsupporting
confidence: 88%
“… 14–17 Further, health status, presence of chronic conditions, and receiving advice from health care professionals are documented factors associated with vaccine uptake. 17 Overall, results from our multivariable regression models were generally consistent with several previous studies that have reported associations between demographic characteristics, health status, and/or health care utilization behaviors and receipt of influenza vaccination, 14–17 Tdap vaccination, 15,18 HZ vaccination, 9,19 or pneumococcal vaccination. 20 …”
Section: Discussionsupporting
confidence: 88%
“…In our study, we observed that self-reported tetanus vaccination coverage decreased with age, with older immigrants (≥65 years of age) reporting a tetanus vaccination coverage of only 58.1% (95% CI: 45.0–70.1). This finding is in line with other studies conducted among immigrants [9,18]. As this decrease with age was also observed among Portuguese natives (data not shown), it would be beneficial to carry out a vaccination catch-up campaign targeting older age groups, regardless of an individuals’ immigration status.…”
Section: Discussionsupporting
confidence: 91%
“…Adult immigrants with the highest household income per adult were less likely to report tetanus vaccination when compared to those with the lowest income. This finding is contrary to other studies conducted among adult immigrants [18], and in the general adult population [13]. However, this is in line with our belief that financial barriers are not a factor associated with vaccination uptake because vaccines included in the Portuguese NIP are free of charge.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…At-risk patients include individuals over 50 years old and immigrants who may not have been fully immunized 13,14. As pointed out by Sanchez-Gonzalez et al, the latter group includes “all foreign-born, irrespective of their birthplace, citizenship, language and years of residence in the United States.” 8 According to the 2010 U.S. census, 12.9% or 40 million people in the U.S. are foreign born7 and as of 2016, 49.2 million Americans are 65 years or older 15. It is imperative to scrutinize the immunization history in these high-risk populations and administer immunoglobulin and tetanus vaccine as recommended.…”
Section: Resultsmentioning
confidence: 99%